The types of speaking errors students in intermediate intensive english I commit, their causes and techniques to correct them - Elías Quijano, Susan Edith; Martínez Cabrera, Gloria Marisol; Pérez Ascencio, Franco Alberto; Rosales Baltes, Andrés Roberto; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2011)
Everyone commits errors when learning a second language. Even native speakers when they speak in their own language. Therefore, teachers and students in the teaching/learning process do not have to get surprised when they commit such errors. Everyday in the learning process learners are prone to make errors whenever they try to express new utterances. Teaching English to students in intermediate level is a challenge because everyone has different interests and needs so teachers should look for several ways of motivating them to get interested in the acquisition of the second language. Besides that, teachers have to take into account that in this level speaking errors are committed frequently since students have not had enough contact with the target language and some of them are still in the basic level. During the leaning process students commit different kinds of errors such as; omission, addition, ordering and selection. However, teachers have to be careful when correcting those errors without discouraging them. There are many correction techniques to correct those kinds of speaking errors, for instance; pointing, repeating, gesturing, cuing, and others that the teachers can use in an EFL classroom. On the other hand, teachers have to pay attention to the factors behind of speaking errors. These are causes why students in intermediate level commit speaking errors such as; interference with mother tongue, generalizing English grammar rules among others. Therefore, this research is presented with the purpose of giving readers some choices to be used while facing speaking errors in an EFL classroom made up of the intermediate English students.
Anexos: instrumentos de la investigación.
Thesis in order to obtain the degree of -- (Licenciado en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2011
Audiencia general.
La tesis también está en formato digital.
Keywords: Inglés -- palabras y frases; Inglés -- Enseñanza; Adquisición de segundo lenguaje